Reengineering of 7-dehydrocholesterol biosynthesis in Saccharomyces cerevisiae using combined pathway and organelle strategies - Wei, Wenqian; Gao, Song; Yi, Qiong; Liu, Anjian; Yu, Shiqin; Zhou, Jingwen (Frontiers in Microbiology, 2022)
7-Dehydrocholesterol (7-DHC) is a widely used sterol and a precursor of several costly steroidal drugs. In this study, 7-DHC biosynthesis pathway was constructed and modified in Saccharomyces cerevisiae. Firstly, the biosynthesis pathway was constructed by knocking out the competitive pathway genes ERG5 and ERG6 and integrating two DHCR24 copies from Gallus gallus at both sites. Then, 7-DHC titer was improved by knocking out MOT3, which encoded a transcriptional repressor for the 7-DHC biosynthesis pathway. Next, by knocking out NEM1 and PAH1, 7-DHC accumulation was improved, and genes upregulation was verified by quantitative PCR (qPCR). Additionally, tHMG1, IDI1, ERG2, ERG3, DHCR24, POS5, and CTT1 integration into multi-copy sites was used to convert precursors to 7-DHC, and increase metabolic flux. Finally, qPCR confirmed the significant up-regulation of key genes transcriptional levels. In a 96 h shaker flask fermentation, the 7-DHC titer was 649.5 mg/L by de novo synthesis. In a 5 L bioreactor, the 7-DHC titer was 2.0 g/L, which was the highest 7-DHC titer reported to date. Our study is of great significance for the industrial production of 7-DHC and steroid development for medical settings.